Impact Assessment of Farm Diversification Schemes in Haryana, India - Elizabeth Jose; K.Ponnusamy (Journal of Extension Education, 2023)
Green revolution was capable of mitigating hunger and malnutrition but it had reportedly made a negative impact in terms of soil and water degradation. Diversification was also seen as one of the solutions to problems brought out by green revolution. As part of farm diversification, the Haryana government has initiated programmes like Mera Pani Meri Virasat (MPMV), Crop Cluster Development Programme (CCDP), Bhavantar Bharpayee Yojana (BBY) etc. This study highlights the impact of MPMV Scheme in a detailed way. It was undertaken in three agro ecological zones of the Indian state of Haryana. One district from each agro- ecological zone was chosen. From each district, 60 farmers were contacted. The study reveals that there is only limited acceptance of new diversification schemes among farmers as it is reflected in their area of adoption. Adequate amount of incentives and timely provision of the compensation amount are likely to further improve the utilization of these programmes among farmers.